Determinant Micro Small and Medium Enterprises Success in Yogyakarta: The Role of Using Accounting Information - Winda Lestari; Amir Hidayatulloh (Politeknik Negeri Madiun, 2019)
This study aims to analyze influence of personal skills, social skills, and the use of accounting information on the success of business in MSMEs. The population of this study is MSMEs in Yogyakarta city. The sampling technique used purposive sampling, with criteria of MSMEs that had been established or operated for five years. Data collection uses a survey method by distributing questionnaires. Respondents of this study amounted to 108 respondents. The data analysis technique of this study uses multiple linear regression analysis with the help of SPSS tools. The result obtained by this study is that the success of business in MSMEs is influenced by personal skill, social skill, and the use of accounting information.